Construction technology 2 industrial and commercial building - Riley, Mike 1964-; Cotgrave, Alison (Palgrave Macmillan, 2014)
This work provides a single text to support the learning process associated with the study of the construction of industrial and commercial buildings. The text includes a series of learning sessions or modules covering individual components of the topic